SPESIALISASI AUDITOR SEBAGAI PEMODERASI PENGARUH AUDIT TENURE DAN UKURAN KAP PADA AUDIT REPORT LAG - Julita Diastiningsih, Ni Putu; Tenaya, Gede Agus Indra (E-Jurnal Akuntansi; Vol 18 No 2 (2017), 2017)
Auditor specialization is expected can improve the influence of audit tenure and size of public accounting firm so that can minimalize audit report lag . The purpose of the study is to determine the influence of audit tenure and size of public accounting firm with audit report lag and use auditor specialization as a moderating variable. Study use manufacturing companies listed in Indonesia Stock Exchange in 2011-2015. Sample obtained by 265 companies by nonprobability sampling method use purposive sampling. The data analysis technique is used moderated regression analysis. The result is audit tenure give positive influence on audit report lag , and size of the public accounting firm give negative influence on audit report lag . Auditor specialization moderated the influence of audit tenure give shorter audit report lag . Auditor specialization can moderated the influence of audit tenure and size of public accounting firm on audit report lag .
Keywords: audit report lag, audit tenure, size of public accounting firm, and auditor specialization.